(untitled) (Research, Society and Development, 2022)
Introduction. Neonatal sepsis is an infectious pathology with a high morbidity and mortality rate, which occurs until the 28th day of life and can be characterized as early when it occurs until the first 72 hours of life and late when it occurs after that time and usually has clinical symptoms associated with systemic disorders, and microorganism cultures are a great help in diagnosis and treatment is performed in a hospital environment. Method. A 55-item form was applied to analyze a total of 273 patients diagnosed with neonatal sepsis. Statistical Package for the Social Sciences was used for data analysis. Objective. To present the data of significant pattern of epidemiology in the Hospital Santa Isabel, having a comparison with the current literature. Results. Significance and agreement was found in the literature with the data analyzed on birth characteristics (birth weight and prematurity), also direct relation to the type of sepsis and its characteristics, as well as vitality evaluation at birth and invasive procedures performed and its association with the patient’s outcome. Conclusion. Low birth weight, prematurity, wiping below 7 and invasive procedures are the major negative predictors for newborn survival.